Consumer intention towards online purchasing in Johor Bahru / Syed Mohamed Syahir Syed Hamid and Noor Hananie Ab Malek - Syed Hamid, Syed Mohamed Syahir; Ab Malek, Noor Hananie (2015)
This study is to determine the relationship between factors that influence consumer intention towards purchasing products from online vendors. It means, a research is done to identify which factor affect the most in influencing consumer online purchase intention. Online shopping has never been more popular than nowadays. Use of the Internet for retail shopping has expanded immensely in recent years and has had a profound influence on the shopping process for many consumers. Social media is being used by vendor as an online retail site. Originally, people are using social media for own personal purpose like chatting, share pictures and getting knows with other people. But today, people have utilized it for business matter like online shopping. In this study, the researcher used questionnaire as a method to collect the data by distributing it to respondents around Johor Bahru. The population of Johor Bahru is 1.3 million. In gathering the data, 60 set questionnaires had been distributed. After the questionnaires have been collected and analyzed, it can be seen that there is no strong relationship between the dependent variable and independent variable. The result shows no significance between vendor trust, brand trust and product trust towards online purchase intention.